2015
DOI: 10.1051/0004-6361/201425169
|View full text |Cite
|
Sign up to set email alerts
|

Solar surface rotation: N-S asymmetry and recent speed-up

Abstract: Context. The relation between solar surface rotation and sunspot activity is still not fully resolved. The sunspot activity has been significantly reduced in solar cycle 24, and several solar activity indices and flux measurements experienced unprecedentedly low levels during the last solar minimum. Aims. We aim to reveal the momentary variation of solar surface rotation, especially during the recent years of reduced solar activity. Methods. We used a dynamic, differentially rotating reference system to determ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…The study has supported southern activity dominated predictions of Verma (1992) and Li et al (2009a) for the current cycle. Zhang et al (2015) studied N-S asymmetry of X-ray flares of class B and higher, during solar cycle 24. They found that the asymmetry was fairly constant and negative (i.e., SH dominant) and SH rotates faster than the NH.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study has supported southern activity dominated predictions of Verma (1992) and Li et al (2009a) for the current cycle. Zhang et al (2015) studied N-S asymmetry of X-ray flares of class B and higher, during solar cycle 24. They found that the asymmetry was fairly constant and negative (i.e., SH dominant) and SH rotates faster than the NH.…”
Section: Resultsmentioning
confidence: 99%
“…The solar N-S asymmetry is considered as one of the most interesting properties of solar activity and studied in many manifestations of solar activity such as flares, prominences, sunspots, filaments, etc. (Howard 1974;Roy 1977;Yadav et al 1980;Swinson et al 1986;Ballester 1987, 1990;Carbonell et al 1993;Oliver and Ballester 1994;Joshi 1995;Javaraiah and Gokhale 1997;Verma 2000;Ataç and Özgüç 2001;Temmer et al 2002;Joshi and Joshi 2004;Ballester et al 2005;Javaraiah and Ulrich 2006;Zaatri et al 2006;Temmer et al 2006;Carbonell et al 2007;Li et al 2009a,b;Gigolashvili et al 2011;Chowdhury et al 2013;Chandra et al 2013;Obridko et al 2014;Joshi et al 2015;Zhang et al 2015;Javaraiah 2016;Bruevich and Yakunina 2017;Deng et al 2017;Gurgenashvili et al 2017;Xie et al 2018;El-Borie et al 2019;Li et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Bai (1987Bai ( , 1988 analysed the coordinates of energetic solar flares based of 5 years of time period and concluded that longitudinal spatial distribution is non-homogeneous. Zhang et al (2007Zhang et al ( , 2008Zhang et al ( , 2015 concluded that the dominant and co-dominant AL contains 80% of C-and X-flares. In GY16, we conducted a similar study based on four solar cycles and we did not find significant co-dominant activity; instead, we found that only the dominant AL contains 60% of the solar flares.…”
Section: Solar Non-axisymmetric Activitymentioning
confidence: 99%
“…Here, the spectral bands are centered at the power peaks above the red-noise level of the global wavelet spectrum. Zhang et al (2015) applied a differentially rotating reference system to determine the bestfit annual values of the differential rotation parameters of active longitudes of solar X-ray flares and sunspots in 1977-2012, and found that the rotation of both hemispheres has been speeding up at roughly the same rate since the late 1990s, with the southern hemisphere rotating slightly faster than the northern hemisphere. Joshi et al (2015) investigated the temporal evolution and north-south asymmetry in the occurrence of soft X-ray flare index during solar cycles 21-23.…”
Section: Introductionmentioning
confidence: 99%